The Association Between Filial Piety and Suicidal Ideation: Findings From a Community-Dwelling Chinese Aging Population - Simon, Melissa A. (J Gerontol A Biol Sci Med Sci, 2014)
BACKGROUND. Suicidal ideation is a public health issue that has a significant impact at the individual, family, community, and societal levels. This study aimed to examine the association between filial piety and suicidal ideation among U.S. Chinese older adults. METHODS. Guided by a community-based participatory research approach, 3,159 community-dwelling Chinese older adults in the Greater Chicago area were interviewed in person between 2011 and 2013. Independent variables were expectations and receipt of filial piety from the older adult’s perspective. Dependent variables were suicidal ideation in the last 2 weeks and last 12 months. Logistic regression analyses were performed. RESULTS. Of the 3,159 participants interviewed, 58.9% were female and the mean age was 72.8 years. After adjusting for age, sex, education, income, medical comorbidities, and depressive symptoms, lower receipt of filial piety was associated with increased risk for 2-week suicidal ideation (odds ratio: 1.07, 95% confidence interval: 1.03–1.11) and 12-month suicidal ideation (odds ratio: 1.07, 95% confidence interval: 1.04–1.11). The lowest tertiles of filial piety receipt was associated with greater risk for 2-week suicidal ideation (odds ratio: 1.95, 95% confidence interval: 1.12–3.38) and 12-month suicidal ideation (odds ratio: 2.17, 95% confidence interval: 1.35–3.48). However, no statistically significant associations were found between overall filial piety expectations and suicidal ideation in the last 2 weeks or in the last 12 months. DISCUSSION. This study suggests that filial piety receipt is an important risk factor for suicidal ideation among U.S. Chinese older adults. Future longitudinal studies are needed to quantify the temporal association between filial piety and suicidal ideation.